The lack of a European public sphere in the debate on the European sovereign debt crisis - Kim Otto; Andreas Köhler (University of Würzburg, Department of Economics, 2016)
The present article examines the coverage of the European actors in the Greek national debt crisis in the German daily newspapers 'Die Welt', 'Bild', 'Frankfurter Allgemeine Zeitung', 'Süddeutsche Zeitung' and 'Die Tageszeitung', as well as on the online platform 'Spiegel Online'. The aim is to capture the extent to which the national German media are Europeanized within the context of coverage of the Greek national debt crisis. The study's results show that it is not really possible to speak of a Europeanized national public sphere in Germany as far as the coverage of the Greek national debt crisis is concerned. In the German media, the European debate was portrayed as a bi-national conflict between the German and Greek governments.
Keywords: H63; H77; Y80; 330; Greek national debt crisis; European public sphere